WRITING ASPIRATIONS IN POETRY: A STUDY ON INDONESIAN STUDENTS' IDENTITY AND REFLECTIVE EXPRESSION IN CREATIVE WRITING - Munthe, Dristyana; Boeriswati, Endry; Supriyana, Asep (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to evaluate the practice of writing poetry as a means of reflective expression and articulation of students' aspirations in the context of the Independent Curriculum in Indonesian subjects. This study analysed 36 poems by high school students, each inspired by a single aspiration-themed word, to explore how the texts reflect their identity, personal values, and hopes for the future. This study uses a qualitative approach with thematic, stylistic, and reflective-narrative content analysis techniques to examine aspects of diction choice, poetic structure, and affective and expressive dimensions in poetry. The analysis results show that most poems display strength in expressing emotions, using personal diction, and having the courage to voice dreams authentically. However, weaknesses were also identified in poetic structure, cohesion between lines, and the richness of language style. These findings suggest that poetry can serve as an unconventional assessment tool capable of revealing reflective aspects of students, which are often overlooked in conventional cognitive assessments. Thus, writing poetry supports creative literacy and strengthens the curriculum's alignment with expressing students' identities as independent learners.